Ion-Sieving Dual-Network Hydrogel Electrolytes Couple Accelerated Ion Transport with Iodide Shuttle Suppression in Aqueous Zn–I2 Batteries - Chen, Ming; Cheng, Jia; Zhao, Yixin; Fu, Wei; Li, Wen; Zhu, Yunhai; Meng, Fanlu (Nano-Micro Letters, 2026)
Aqueous Zn–I2 batteries hold significant promise for large-scale energy storage applications; however, their practical implementation is constrained by coupled interfacial instabilities, including Zn dendrite growth, parasitic hydrogen evolution and polyiodide shuttling. Here we report a dual-network hydrogel electrolyte that stabilizes Zn and iodine chemistries through a synergistic, cross-scale design spanning molecular conformation regulation, charge microenvironment engineering and network topology control. By precisely tailoring the local charge microenvironment, the hydrogel electrostatically excludes polyiodide species to mitigate the shuttle effect, while simultaneously constructing low-energy pathways for Zn2+ migration, enabling differentiated ion regulation. The interconnected porous architecture further homogenizes ionic conduction and modulates three-dimensional Zn2+ flux at the Zn interface, delivering dendrite-free Zn plating/stripping for over 3500 and 800 h at areal capacities of 1 and 10 mAh cm−2, respectively. In Zn–I2 full cells, stable cycling is maintained for 20,000 cycles at a high rate of 10 C. This work establishes an integrated molecular-to-mesoscale electrolyte design strategy for advancing highly stable aqueous Zn–I2 batteries. Highlights: 1 A dual-network hydrogel electrolyte integrates the mechanical robustness of polyacrylamide with functional groups from carboxymethyl chitosan (CMCS), overcoming the single-network trade-off between ionic conductivity and mechanical integrity. 2 Introducing tert-butylamine suppresses amino group protonation and increases carboxyl group electronegativity, thereby directionally tuning the Zn2+ transport microenvironment. 3 Uniform pores and high ionic conductivity promote a homogeneous Zn2+ flux to suppress dendrite growth, while electronegative carboxylate groups in CMCS inhibit polyiodide shuttling through electrostatic repulsion.